2020
DOI: 10.1136/bmjgast-2020-000494
|View full text |Cite
|
Sign up to set email alerts
|

Wide-area transepithelial sampling in adjunct to forceps biopsy increases the absolute detection rates of Barrett’s oesophagus and oesophageal dysplasia: a meta-analysis and systematic review

Abstract: BackgroundWide-area transepithelial sampling (WATS) is a new technique that uses an abrasive brush to obtain samples from a larger surface area of the oesophagus. Studies have shown promising results that WATS in adjunct to forceps biopsy (FB) increases the detection rate of Barrett’s oesophagus (BE) as well as oesophageal dysplasia (ED). We conducted a systematic review and meta-analysis to compare the detection rates of BE and ED between FB and WATS in adjunct to FB.MethodsA Literature search was done using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this low-risk population, HGD was not detected in any patients by FBs; however, WATS 3D detected a single case of EAC missed by FBs ( 30 ). A recent meta-analysis also strongly supported the adjunctive use of WATS 3D to FB in BE screening and surveillance ( 33 ).…”
Section: Wats 3d Literature Review and Clinical Impactmentioning
confidence: 90%
“…In this low-risk population, HGD was not detected in any patients by FBs; however, WATS 3D detected a single case of EAC missed by FBs ( 30 ). A recent meta-analysis also strongly supported the adjunctive use of WATS 3D to FB in BE screening and surveillance ( 33 ).…”
Section: Wats 3d Literature Review and Clinical Impactmentioning
confidence: 90%
“… 80 Several studies demonstrated that WATS significantly improved the detection of both BE and esophageal dysplasia (Table 2 ). 80 , 81 , 82 , 83 , 84 , 85 Thus, in a prospective multicenter community‐based study enrolling 12,899 patients, Smith MS et al 80 showed that adding WATS to routine forceps biopsy raised the yield of dysplasia detection from 0.68% to 2.33% and increased the overall detection of dysplasia by 242% (95% CI 191%–315%). Rate of BE detection by forceps biopsy was 13.1% and WATS raised it to 33% increasing the overall detection of BE by 153% (95% CI 144%–162%).…”
Section: Wide Area Transepithelial Sampling With Computer‐assisted Three‐dimensional Analysis (Wats)mentioning
confidence: 99%
“…19 A recent systematic review and meta-analysis with pooled data from 20 392 endoscopies across 11 studies also showed significant increases in detection of both BE and dysplasia when WATS was used in addition to FB. 35 A study by Raphael et al 36 evaluated whether there was any adjunctive yield of WATS-3D for dysplasia detection after advanced imaging (with HDWLE + NBI + VLE) plus Seattle protocol biopsies, and revealed that WATS-3D gave an added yield of 34.3%. WATS-3D also appears to be cost-effective when screening for BE based on a recent analysis.…”
Section: Wide-area Transepithelial Tissue Sampling With Computer-assisted 3d Analysis (Wats-3d)mentioning
confidence: 99%